E-Binmas Online Information System - I Ketut Agus Juliandana (JURNAL ILMU KOMPUTER INDONESIA, 2020)
E-Binmas Polres Buleleng Information System was developed to provide the police officer of human relation (bhabinkamtibmas) to collecting and reporting information online. At the beginning of build this system starts from system desingning, database designing and interface desingning. E-Binmas Polres Buleleng Information System are build using PHP programming language and Codeigniter framewok. Sublime Text as script editor and also MySQL for database manager. The system developing goals are hope to be provide the police officer of human relation of Polres Buleleng to collect the field information and improving the work capacity of human relation police unit (Satuan Binmas) Polres Buleleng to protec the social security of Buleleng regency.